A 2-year longitudinal seroepidemiological evaluation of toxoplasma gondii antibodies in a cohort of autochthonous sheep from central Portugal - Almeida, Daniela (2021)
Funding Information: Funding: This research was funded by the National Funds by FCT—Portuguese Foundation for Science and Technology, under the project UIDB/04033/2020. PGdS thanks FCT for the financial support of her PhD work (2020.07806.BD) contract through the DOCTORATES 4 COVID-19 program. Publisher Copyright: © 2021 by the authors.